1989
DOI: 10.1111/j.1365-2141.1989.tb07754.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to platelet glycoproteins in patients with disease‐related immune thrombocytopenia

Abstract: Although increased platelet destruction and elevated platelet-associated IgG have been shown in patients with lymphomas and various autoimmune diseases, such as systemic lupus erythematosus (SLE), there have been few studies evaluating autoantibodies against platelet-specific antigens. We evaluated 24 patients retrospectively with disease-related thrombocytopenia (12 with lymphoproliferative diseases and 12 with various autoimmune disorders) using a recently reported antigen-specific assay. Autoantibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…Antibodies against a variety of platelet proteins, particularly the GPIIb/IIIa complex, are often seen in patients with SLE [17][18][19] and may be related to the thrombocytopenia in these patients. In this paper, we will present the first case of SLE who acquired a platelet-aggregating anti-GPVI antibody and showed a defective collagen-induced platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies against a variety of platelet proteins, particularly the GPIIb/IIIa complex, are often seen in patients with SLE [17][18][19] and may be related to the thrombocytopenia in these patients. In this paper, we will present the first case of SLE who acquired a platelet-aggregating anti-GPVI antibody and showed a defective collagen-induced platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of antibodies has revealed that GP IIbIIIa and GP IbIX are the most immunogenic of the platelet glycoproteins (van Leeuwen et al, 1982;Beardsley et al, 1984;Woods et al, 1984a & b;McMillan et al, 1987;Tomiyama et al, 1987Tomiyama et al, & 1989Berchtold et al, 1989a;Kokawa et al, 1993;Deckmyn et al, 1994;He et al, 1994;Stockelberg et al, 1995;Kiefel et al, 1996).…”
Section: Platelet Antibodiesmentioning
confidence: 99%
“…Nevertheless, the detection of direct platelet eluates requires a selected patient population with a relatively high platelet count. Immunobead assay Disease-related TP 19 9 (47) 2 (11) Berchtold et al, 1989c Immunoprecipitation ITP 6 4 Tomiyama et al, 1990 Immunobead assay ITP children ITP adults 41 16 40 (98) 14 (88) 1 (2) 2 (13) Imbach et al, 1991 MAIPA Immune TP 29 21 (72) 22 (28) 14 (48) Kiefel et al, 1991 ELISA ITP 71 25 (35) 10 (14) Kokawa et al, 1991 Immunobead assay ITP In remission 53 17…”
Section: Detection Of Gp-specific Pa-iggmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute ITP is predominantly a disease of childhood, characterized by the abrupt onset of severe thrombocytopenic purpura, which often occurs with a history of viral infection. Most cases are of short duration and recover spontaneously, usually within 1-2 months, but only in 10-20% of the cases, TP becomes chronic, resembling adult ITP (Cohn, 1976;Berchtold et al, 1989).…”
mentioning
confidence: 99%